Organic carbon sequestration in global croplands: evidenced through a bibliometric approach - Abrar, Muhammad Mohsin; Waqas, Muhammad Ahmed; Mehmood, Khalid; Fan, Ruqin; Memon, Muhammad Suleman; Khan, Muhammad Ajmal; Siddique, Nadeem; Xu, Minggang; Du, Jianjun (Frontiers in Environmental Science, 2025)
Increasing soil organic carbon (SOC) in cropland soils improves soil health and water quality, crop productivity, and resilience to climate-driven changes by influencing key soil processes. However, research on cropland SOC sequestration based on bibliometric analyses of highly cited documents is lacking. This bibliometric study investigated the current status and development characteristics, research impact, intellectual base, and research hotspots of highly cited cropland SOC sequestration research using the Web of Science Core Collection databases from 2012 to 2022. The analysis and visualization tools such as Biblioshiny, VOSviewer, CiteSpace, Power BI, and Flourish Studio, provided a comprehensive approach for research evaluation, identifying trends, and knowledge mapping of cropland SOC sequestration research. The findings indicate that the United States and China dominate global research, with the Chinese Academy of Sciences as the leading institution. Key journals include Soil Biology and Biochemistry and Geoderma. e. The trend topic graph indicated that “soil organic carbon” and “soil organic matter” are the most persistent themes since 2015. In contrast, recent research focuses on “climate change mitigation,” “soil health” and “soil aggregation”. Moreover, burst analysis of citation and keywords revealed significant insights into the potential role of microbes in transforming and stabilizing soil organic matter. The findings of the present study emphasized that adopting management practices aimed at enhancing carbon inputs increases C sequestration in croplands, thus improving soil health and help in advancing Sustainable Development Goals (SDGs).